Audio-visual-olfactory immersive digital nature exposure for stress and anxiety reduction: a systematic review on systems, outcomes, and challenges - Lopes, Marilia K. S.; Falk, Tiago H. (Frontiers in Virtual Reality, 2024)
Evidence supporting the benefits of immersive virtual reality (VR) and exposure to nature for the well-being of individuals is steadily growing. So-called digital forest bathing experiences take advantage of the immersiveness of VR to make individuals feel like they are immersed in nature, which has led to documented improvements in mental health. The majority of existing studies have relied on conventional VR experiences, which stimulate only two senses: auditory and visual. However, the principle behind forest bathing is to have one stimulate all of their senses to be completely immersed in nature. As recent advances in olfactory technologies have emerged, multisensory immersive experiences which stimulate more than two senses may provide additional benefits. In this systematic literature review, we investigate the multisensory digital nature setups used and their psychological and psychophysiological outcomes; particular focus is placed on the inclusion of smells as the third sensory modality. We searched papers published between 2016 and April 2023 on PubMed, Science Direct, Web of Science, Scopus, Google Scholar, and IEEE Xplore. Results from our quality assessment revealed that the majority of studies (twelve) were of medium or high quality, while two were classified as low quality. Overall, the findings from the reviewed studies indicate a positive effect of including smells to digital nature experiences, with outcomes often comparable to conventional exposure to natural environments.The review concludes with a discussion of limitations observed in the examined studies and proposes recommendations for future research in this domain.